The Effect of Traditional Games on Participation of Elementary School Students in Physical Education - Rizal Ahmad Fauzi; Ayi Suherman; Dewi Susilawati; Entan Saptani; Aam Ali Rahman (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
Technological developments have positive and negative impacts. One of the negative impacts is the increasing amount of screen time children spend. So that children’s participation in learning physical education is disrupted. The purpose of this study, among others, is to see the effect of traditional games on the participation of elementary school students in learning physical education. The method used is quasi-experimental with one group pre-test and post-test design. The research sample amounted to 43 people, consisting of 20 male students and 23 female students. The sample is grade 5 students aged 10-11 years. This research instrument uses a sports participation questionnaire with a scale of 2 “yes” or “no.” the dimensions of the instrument include (1) Pre-implementation, (2) Implementation, and (3) Post-implementation/evaluation. The results showed a p-value = 0.000 < 0.05; this means that there is a difference between the average value of the pre-test and the average value of the post-test. This study concludes that traditional games affect the participation of elementary school students in learning physical education.